Counselling Career with Artificial Intelligence: A Systematic Review - Muhammad, Rifqi; Patriana, Patriana; Yusrain, Yusrain; Astaman, Astaman; Manja, Manja (Universitas Muhammadiyah Metro, 2024)
This systematic review aimed to review empirical research on leftist counseling careers with AI. This research applied SLR and evaluated Scopus, PubMed, Google Scholar, and Crossref databases. The results showed n = 43 on Scopus, n = 3 on PubMed, n = 70 on Google Scholar and n = 3000 on Crossref. After PRISMA analysis, n = 14 studies were included in the review. Studies examining career counseling with AI: (Carson et al., 1999; Crowley, 1992; Guleria & Sood, 2023; Hendahewa et al., 2006; José-García et al., 2022; Joshi et al., 2020; Lee et al., 2018; Liu, 2023; Nazareno et al., 2019; Suresh et al., 2021; Westman et al., 2021a; Yan et al., 2019; Zhang et al., 2022; Zhang & Zheng, 2022). The manuscripts' publication years also varied: 1992, 1999, 2006, 2018, 2019, 2020, 2021, 2022, and 2023. This study was conducted in Namibia, the USA, the UK, China, Romania, India, Sri Lanka, the Philippines, South Korea, and Finland. System: computer algorithm, artificial neural network, AIED, C3-IoC, Facebook Messenger, iAdvice, and online career counselor system (Chatbot and machine learning). Objectives: career prediction, career matching with companies, career selection, career guidance, and career decision-making. Requirements: AI supports students in study and career planning, self-management, and accessible and timely advice, whether delivered by AI or humans. AI is a technical subject with personal, career, and social implications; it is essential for developing academic and professional thinking and career planning in the AI era.